2018
DOI: 10.1007/s11356-018-3814-0
|View full text |Cite
|
Sign up to set email alerts
|

Studies on CWL with glycerol for combustion process

Abstract: Findings of more efficient energy recovery methods are focused on composite fuels consisting of coal, water, and waste materials. The use of such slurry fuels has enormous environmental benefits due to the potential for waste utilization and low emissions of harmful oxides to the atmosphere during the combustion process. In this study, we report the effect of waste glycerol on the rheological properties of coal-water fuel (CWS). The addition of glycerol to CWS increases the viscosity (from 45.5 to 184.2 mPa·s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…By-products of the textile and meat industries, such as wool, horns, hooves and feathers contain a large proportion of keratin. 1,2 Keratin is a protein that has, due to its biodegradability and biocompatibility, recently become increasingly important. 3 Wool is often used in textile industry due to its excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By-products of the textile and meat industries, such as wool, horns, hooves and feathers contain a large proportion of keratin. 1,2 Keratin is a protein that has, due to its biodegradability and biocompatibility, recently become increasingly important. 3 Wool is often used in textile industry due to its excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition to proteins, wool contains small proportion of lipids, mineral salts, nucleic acid residues and carbohydrates. 2 Keratin has an extremely high potential to be used for the development of new products in the pharmaceutical, medical, cosmetic and biotechnology industries. Keratin from wool can be used for several forms of gels, microfibres, films, sponges, bulk materials, in wound healing, drug delivery, tissue engineering and medical devices.…”
Section: Introductionmentioning
confidence: 99%
“…According to Polish strategic documents and forecasts, this is mainly related to energy security and other economic and social considerations. Therefore, there are many projects and analyses in Poland which focus on the reduction of the impact of coal-based electricity generation on the environment, including on the implementation of water-coal slurry [2], blue coal [3], coal gasification [4] or carbon capture and storage (CCS) technology [5] as well as reducing the emission of heavy metals like Hg [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the addition of 20% of glycerol to CWF reduces the fuel pour point to −5 C, which is important for its transportation and storage. 18 The maximum possible glycerol content in the coalwater fuel is 21%, and fuel's viscosity is up to 1.5 PaÁs. It is shown in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that if glycerol is added to CWF, an increase in fuel viscosity (from 0.455 to 1.842 Pa·s) and density (from 1.08 to 1.11 g/cm 3 ) are observed. Furthermore, the addition of 20% of glycerol to CWF reduces the fuel pour point to −5°C, which is important for its transportation and storage 18 …”
Section: Introductionmentioning
confidence: 99%